2021
DOI: 10.1101/2021.07.08.451677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultra-slow fMRI fluctuations in the fourth ventricle as a marker of drowsiness

Abstract: Vigilance and wakefulness modulate estimates of functional connectivity, and, if unaccounted for, they can become a substantial confound in resting-state fMRI. Unfortunately, wakefulness is rarely monitored due to the need for additional concurrent recordings (e.g., eye tracking, EEG). Recent work has shown that strong fluctuations around 0.05Hz, hypothesized to be CSF inflow, appear in the fourth ventricle (FV) when subjects fall asleep. The analysis of these fluctuations could provide an easy way to evaluate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
(162 reference statements)
4
2
0
Order By: Relevance
“…Spontaneous fluctuations in respiratory volume (RVT), heart rate (HR), peripheral vasculature (low-frequency PPG and PPG pulse amplitude) and pupil dilation signals show strong correlations with the global BOLD signal ( Figure 2C ). Consistent with previous reports of an anti-correlated dynamic between global gray matter BOLD signals and cerebrospinal fluid (CSF) signals (Gonzalez-Castillo et al, 2022; Picchioni et al, 2022), the spatial weights of the global BOLD signal (PC1; Figure 2A ) from the ME-REST and HCP-REST datasets encode an anti-correlated fluctuation between voxels of the ventricles and those of the gray and white matter. Consistent with this pattern, correlations between the time courses of ventricle BOLD signals and the global BOLD signal exhibit strong anti-correlation across subjects ( Figure 2C1 ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Spontaneous fluctuations in respiratory volume (RVT), heart rate (HR), peripheral vasculature (low-frequency PPG and PPG pulse amplitude) and pupil dilation signals show strong correlations with the global BOLD signal ( Figure 2C ). Consistent with previous reports of an anti-correlated dynamic between global gray matter BOLD signals and cerebrospinal fluid (CSF) signals (Gonzalez-Castillo et al, 2022; Picchioni et al, 2022), the spatial weights of the global BOLD signal (PC1; Figure 2A ) from the ME-REST and HCP-REST datasets encode an anti-correlated fluctuation between voxels of the ventricles and those of the gray and white matter. Consistent with this pattern, correlations between the time courses of ventricle BOLD signals and the global BOLD signal exhibit strong anti-correlation across subjects ( Figure 2C1 ).…”
Section: Resultssupporting
confidence: 87%
“…First, is the anti-correlated fluctuations in BOLD signals observed between gray/white matter tissue and ventricles ( Figure 1 ). While our study did not explicitly measure CSF inflow effects (Fultz et al, 2019), these findings are consistent with anti-correlated fluctuations observed between the CSF (measured from an ROI in the fourth ventricle) and global BOLD signals that become more prominent during periods of low vigilance (Gonzalez-Castillo et al, 2022; Picchioni et al, 2022). Second, is the time-lag or traveling wave structure of spontaneous global BOLD fluctuations and those observed in response to voluntary respiratory changes.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our findings may be related to previous studies identifying a component of the fMRI-BOLD signal related to arousal, but further research is necessary to test if this component and the TRR reflect the same phenomenon ( Chang et al, 2016 ; Özbay et al, 2019 ; Gonzalez-Castillo et al, 2021 ; Goodale et al, 2021 ). One of these studies Goodale et al, 2021 found that the most responsive voxels measured were in the primary sensory cortices, including early visual cortex, and that these voxels alone sufficed for prediction of behavioral performance and an EEG measure of arousal.…”
Section: Discussionsupporting
confidence: 80%